Professional development perceived by youth surfers coaches - doi: 10.4025/reveducfis.v23i3.15320 - Valmor Ramos; Vinicius Zeilmann Brasil; Ciro Goda (Revista da Educação Física)
The aim of the study was to describe how coaches perceive their own professional development in surf and interpret these perceptions according to the specialized literature. A qualitative study was conducted with multiple case studies involving eleven competent coaches of young surfers in Florianópolis, Brazil. Data were collected from structured interviews and semi-structured. For data analysis we used the technique of content analysis. The results show that the coaches give importance to various informal sources of development. The sharing of knowledge, problem solving and observation of other coaches are essential in the construction of professional knowledge. It is concluded that professionals learn from spontaneous engagement in the specific field of surfing and a process of socialization within a socio-cultural context of this sport.